2018
DOI: 10.1186/s13046-018-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

14, 15-EET induces breast cancer cell EMT and cisplatin resistance by up-regulating integrin αvβ3 and activating FAK/PI3K/AKT signaling

Abstract: Background14,15-epoxyeicosatrienoic acid (14,15-EET) is an important lipid signaling molecule involved in the regulation of tumor metastasis, however, the role and molecular mechanisms of 14,15-EET activity in breast cancer cell epithelial-mesenchymal transition (EMT) and drug resistance remain enigmatic.MethodsThe 14, 15-EET level in serum and in tumor or non-cancerous tissue from breast cancer patients was measured by ELISA. qRT-PCR and western blot analyses were used to examine expression of integrin αvβ3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 42 publications
2
87
0
Order By: Relevance
“…Luo et al identified FAK/PI3K/AKT activation in response to 14,15- EET, through the upregulation of avb3 integrin, with the responses attenuated by 14,15-EEZE, a 14,15-EET antagonist. Lastly, the investigators observed that in addition to promoting mesenchymal properties, 14,15-EET also protected breast cancer cells from cisplatin toxicity in vitro and in vivo using a mouse xenograft model (Luo et al, 2018). This is significant because it provides evidence of a novel role for 14,15-EET in cancer progression.…”
Section: Breast Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…Luo et al identified FAK/PI3K/AKT activation in response to 14,15- EET, through the upregulation of avb3 integrin, with the responses attenuated by 14,15-EEZE, a 14,15-EET antagonist. Lastly, the investigators observed that in addition to promoting mesenchymal properties, 14,15-EET also protected breast cancer cells from cisplatin toxicity in vitro and in vivo using a mouse xenograft model (Luo et al, 2018). This is significant because it provides evidence of a novel role for 14,15-EET in cancer progression.…”
Section: Breast Cancermentioning
confidence: 93%
“…Another study examining the effect of 14,15-EET in breast cancer demonstrated that 14,15-EET mediates epithelialmesenchymal transition (EMT) in breast cancer cell lines (Luo et al, 2018). EMT of cells is indicative of their metastatic capability as cells become more migratory and invasive.…”
Section: Breast Cancermentioning
confidence: 99%
“…Ezrin promotes breast cancer progression by modulating AKT signals N Li et al Since EMT is an important component in tumour metastasis and invasion, 23 we next investigate the effect of Ezrin on EMT in BC. Interestingly, we found that when Ezrin was silenced, the BC cells attained an epithelial morphology and lost their migratory capability, whereas Ezrin overexpressed cells acquired a dispersed, spindle-shaped morphology (Supplemental Fig.…”
Section: Ezrin Promotes Bc Metastasis Via Emt In Vitro and In Vivomentioning
confidence: 99%
“…Elevated EET concentrations are associated with co-upregulation of CYP450 epoxygenases CYP2C19 and CYP2J2, FABP4 and FABP5, and adipocyte signaling-related proteins in TNBC tumors [25]. EETs are also important in epithelial-mesenchymal transition (EMT) and resistance via the STAT and AKT signaling pathways [26][27][28][29][30]. From these observations, we hypothesized that FABP4 and FABP5 have dynamic roles in EET-mediated TNBC signaling, particularly in the activation of pathways involved in stromal interaction and metastasis transformation.…”
Section: Introductionmentioning
confidence: 99%